The impact of motivation to lead on team outcomes: the mediating role of leaders’ role satisfaction in China and Germany - Braun, Stephan; Semenkova, Anna; Lalla, Julia; van Dick, Rolf; Hernandez Bark, Alina S. (Frontiers in Psychology, 2025)
IntroductionMotivation to lead (MTL) has been identified as a key predictor of leadership effectiveness. It comprises three distinct facets—affective, calculative, and normative MTL—which differentially impact leadership outcomes. However, we know little about how these facets affect team climate and team effectiveness across cultures and from leader and follower perspectives. Additionally, we examine the influence of role satisfaction with the leader role within this relationship.MethodsWe conducted two complementary studies to examine the effects of MTL on team outcomes. Study 1 involved a German leader sample, while Study 2 comprised follower samples from both Germany and China. We measured affective, calculative, and normative MTL as independent variables, team effectiveness and team climate as dependent variables, and additionally role satisfaction with the leader role as a potential mediator.ResultsOur findings confirmed that the three MTL facets have differential effects on team outcomes. Affective MTL consistently showed positive effects across samples. In contrast, calculative and normative MTL demonstrated mixed effects in the different cultural contexts and whether the perspective was a leader or a follower one. Specifically, normative and calculative MTL were perceived more positively in the Chinese follower sample. Mediation analysis revealed that role satisfaction significantly mediated some of the relationship between MTL and outcomes, but only in Germany.DiscussionThese results suggest that research should focus more on boundary conditions of MTL and its effects. Special consideration should be given to the culture in which MTL is measured and who (followers or leaders) provides these assessments. This could inform more nuanced MTL research as well as enable more effective programs in leadership selection and organizational culture development.